Peningkatan Kompetensi Profesional Guru melalui Supervisi Klinis di MI Candirejo - Sohif Maftahal Luthfi; Rahmat Hariyadi (PT PUSTAKA CENDEKIA GROUP, 2025)
This article focuses on the purpose and implementation of supervision carried out at MI Candirejo to see the improvement of teacher professionalism through clinical supervision with an educational background in accordance with the teaching profession. The research in this article uses descriptive qualitative research with a Library Research approach, namely by reading, examining and reviewing journals and writing sources that are closely related to the issues discussed. The results of this study indicate that there are findings of 2 teachers with educational backgrounds who graduated from MI to become teachers at MI Candirejo, this will affect the professionalism of teachers in educating and teaching. Related to the four professional competencies of the teacher. The school's efforts to improve teachers' professional performance include requiring teachers who attend training to socialise with other teachers at school on Saturdays and sending them to attend training outside of general and service-based training. The centre fosters the school's efforts to improve the four competencies. The results of initial observations and school profile data of MI Candirejo, Using the term ‘bottom up’ is more for teachers who ask questions, especially for new teachers who are not familiar with the culture and character of the school. On average, only small problems are solved by asking the right person to fix it so that the teacher can fix the problem. In MI Candirejo, clinical supervision to improve teacher professionalism is very adaptive, starting from planning which is only communicated to teachers in weekly routine meetings by the principal. It can be concluded that clinical supervision will create teacher professionalism through coaching conducted by the principal and follow-up conducted by the supervisor as well as the participation of senior teachers and also the vice curriculum at school.